Some Like It Transitive: Remarks On Verbs Of Liking And The Like In The Saami Languages - Kittilä, Seppo (Zenodo, 2018)
Canonical DOM is rather uncommon in the Saami languages (Uralic), and the only clear instances of this are attested in South Saami where definiteness does determine the coding of objects in the plural. On the other hand, the coding of experiencer verbs (e.g., 'like', 'care' and 'fear') displays variation in this regard across Saami languages. With the North Saami verb \textit{liikot